Charakterystyka wybranych cech morfologicznych świerków wpływających na ich stabilność, ukształtowanych w wyniku stosowania różnych rębni w borze górnoreglowym na Pilsku - Jaworski, Andrzej; Pach, Maciej (Leśne Prace Badawcze, 2011)
The morphology of trees was studied in four sample plots located within the Pilsko high mountain spruce forest. Between the years 1950–1970 a single-tree selection system (Einzelplenterung) was used in the stands Pilsko 1 and 2, whereas in a third stand, Pilsko 3, selection was by group cutting (Gruppenplenterung). The tree-stand Pilsko 4 was generated by artificial restocking of a clear-cut area. The live crown ratio, coefficient of slenderness (h/d) and vitality of these four stands was compared. Group cutting (Pilsko 3), resembling a mountain selection system, produced the highest live crown ratio, lowest coefficient of slenderness (h/d) and highest vitality index of the four tree-stands examined. The spruces grown in the diversified tree-stands where a single-cutting system was used had features indicative of lower stability. In the artificial one-storey and even-aged stands, the two features that determine tree stability (namely, live crown ratio and coefficient of slenderness) had the worst values compared the remaining three stands. Consequently, to improve the stability of high mountain spruce forests in the Beskidy Mountains, under active environmental protection, we recommend the creation of groups within the forest, thus producing an irregular shelterwood system of group cuttings within a belt of closed forest, or a mountain selection system within a loose spruce forest.